Training-Induced Neural Plasticity in Youth: A Systematic Review of Structural and Functional MRI Studies - Tymofiyeva, Olga; Gaschler, Robert (Frontiers in Human Neuroscience, 2021)
Experience-dependent neural plasticity is high in the developing brain, presenting a unique window of opportunity for training. To optimize existing training programs and develop new interventions, it is important to understand what processes take place in the developing brain during training. Here we systematically review MRI-based evidence of training-induced neural plasticity in children and adolescents. A total of 71 articles were included in the review. Significant changes in brain activation, structure, microstructure, and structural and functional connectivity were reported with different types of trainings in the majority (87%) of the studies. Significant correlation of performance improvement with neural changes was reported in 51% of the studies. Yet, only 48% of the studies had a control condition. Overall, the review supports the hypothesized neural changes with training while at the same time charting empirical and methodological desiderata for future research.